Thermal and kinetic characteristics of pyrolysis and combustion of three oil shales. (June 2015) - Bai, Fengtian; Sun, Youhong; Liu, Yumin; Li, Qiang; Guo, Mingyi
Highlights: Oil shales were investigated using isoconversional methods. FTIR and XRD tests identified the hydrocarbons and minerals in oil shale. Not a remarkable change in mass loss with heating rate. The diverse compositions of oil shale led to different thermal/kinetic behaviors. Nongan oil shale exhibited markedly high thermal stability and activation energy. Abstract: High temperature plays an important role in the conventional utilization of oil shale regardless of refining or burning. This paper describes the thermal and kinetic characteristics of pyrolysis and combustion of Huadian, Fushun, and Nongan oil shales from three northeast basins of China, particularly Nongan oil shale in Songliao Basin. Fourier transform-infrared spectroscopy and X-ray diffraction were performed to characterize the hydrocarbons and minerals in oil shale. Non-isothermal thermogravimetric analysis was used to investigate the pyrolysis and combustion behaviors of oil shales. The activation energy was calculated using Friedman, Starink, distributed activation energy model, and Ozawa iterative methods. Results indicated that the thermal decompositions of three oil shales exhibit multiple reaction processes, especially combustion process, and the diversity of organic and mineral compositions in oil shale have considerable effects on the thermal behavior and kinetic characteristics of the three samples. Novel exploitation technology for oil shale in Songliao Basin needs to be proposed.